Back Cover: Poly(benzoxazine) as an Immobilization Matrix for Miniaturized ATP and Glucose Biosensors (ChemElectroChem 4/2017). Issue 4 (23rd March 2017) - Ziller, Charlotte; Lin, Jing; Knittel, Peter; Friedrich, Laura; Andronescu, Corina; Pöller, Sascha; Schuhmann, Wolfgang; Kranz, Christine
Abstract : The Back Cover picture shows a scheme of the improved ATP microbiosensor based on poly(benzoxazine) entrapment of enzymes for the detection of ATP at mechanically stimulated osteoblastic cells. More information can be found in the Article by C. Kranz and co‐workers onpage 864 in Issue 4, 2017 (DOI:10.1002/celc.201600765 ).